C-Terminal splice variants Of P/Q-type Ca2+ channel Cav2.1 subunits are differentially regulated by Rab3-interacting molecule proteins - Wong Chee Fah, Hirano Mitsuru, Takada Yoshinori, Yamaguchi Kazuma, Kotani Hiroshi, Kurokawa Tatsuki, Mori Masayuki X., Snutch Terrance P., Ronjat Mich (N/A, 2017)
C-Terminal splice variants Of P/Q-type Ca2+ channel Cav2.1 subunits are differentially regulated by Rab3-interacting molecule proteins by Wong Chee Fah, Hirano Mitsuru, Takada Yoshinori, Yamaguchi Kazuma, Kotani Hiroshi, Kurokawa Tatsuki, Mori Masayuki X., Snutch Terrance P., Ronjat Mich